DETERMINATION OF MERCURY(II) ION IN WASTEWATER BY INVERSION VOLTAMMETRIC METHOD (Proceedings of International Educators Conference, 2024)
Development of convenient methods for the determination of mercury ions in micro-quantities from the composition of wastewater by inversion-voltammetric method in complex mixtures. Evaluation of metrological characteristics of determination of mercury(II) ion by inversion voltammetric method has been improved.